Short- and long-term outcomes of laparoscopic low anterior resection with “dog ear” invagination anastomosis for mid and distal rectal cancer a propensity score matched analysis - Zhang, L.; Xie, Z.; Gong, L.; Lv, X. (Frontiers in Surgery, 2023)
Background The lateral intersecting margin (dog-ear) was a weak spot of the double stapled technique (DST), We designed “dog-ear” invagination anastomosis (DAIA), which could eliminate the “dog-ear” in laparoscopic anterior resection. Patients and methods A total of 202 patients underwent elective curative LLAR + DST (n = 143) or LLAR + DAIA (n = 59) were enrolled in the study. Propensity score matching (PSM) was used to minimize the adverse effects. The clinical data between LLAR + DST and LLAR + DAIA was compared, and the effect of factors on overall survival (OS) and disease-free survival (DFS) was analyzed. Results After PSM, 53 pairs of the LLRA + DST and LLRA + DAIA patients were enrolled in the study. The LLRA + DAIA group has a higher level (3.50 ± 1.03 vs. 2.87 ± 1.10, P = 0.01) of the anastomosis than that of the LLRA + DST group. Patients in LLAR + DAIA group have a lower incidence of protecting loop ileostomy compared to LLAR + DST group (20.75% vs. 5.66%, P < 0.05). The LLRA + DAIA patients presented better rates of LARS compare to LLRA + DST patients at 6 months (major LARS 37.74% (n = 20) vs. 67.93% (n = 36); P = 0.007) and 12 months (major LARS 13.21% (n = 7) vs. 20.37% (n = 11); P = 0.03) after surgery. The OS and DFS rates were similar (P > 0.05). Conclusion Laparoscopic low anterior resection with “dog-ear” invagination anastomosis technique are well-established procedures for patients with low rectal cancer. “Dog-ear” invagination anastomosis technique may reduce the incidence of protecting loop ileostomy and significantly affect LARS score, and demonstrate a positive impact on the quality of life after surgery.